PERMOHONAN PERWALIAN YANG DILAKUKAN IBU KANDUNG GUNA MENGELOLA DAN IZIN JUAL HARTA WARISAN ANAKNYA YANG MASIH DIBAWAH UMUR (Studi Putusan No:118/Pdt.P/2022/Pn Tjk) - Tami Rusli; Okta Ainita; Arif Nur Rachman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
Abstract The constitution of the Republic of Indonesia Article 1 paragraph (three) Indonesia is a constitutional nation, anyone is no exception due to the fact that delivery is a prison difficulty. based totally on the effects of the studies and dialogue, the techniques for filing programs for guardianship and dealing with the belongings of minors at the Tanjung Karang District court docket (selection observe wide No:118/Pdt.P/2022/Pn Tjk). ought to whole several administrative requirements, the party submits 6 copies of the application, the Officer receives and checks the completeness of the utility, the Officer enters the identity of the birthday party/parties, posita, petitum software inside the SIPP application, assesses and makes the SKUM down payment for the case fee, offers commands to the Petitioner/candidates to deposit the quantity of case expenses indexed inside the SKUM through the precise financial institution. The utility will be finished in less than 1 month from the registration of the case. due to the law, after the guardian is appointed via the Tanjung Karang District court docket choose (choice study No:118/Pdt.P/2022/Pn Tjk), the applicant can take prison action on behalf of his infant who's nonetheless underage to emerge as a dad or mum and this electricity of sale is for looking after the sale/switch of asset rights from the applicant's husband. The father or mother appointed by the courtroom ought to additionally be accountable for all of the moves of the kid under his guardianship and the parent need to additionally represent him in all civil moves.